Nationwide Incidence of Serious Complications of Epidural Analgesia in the United States. Issue 4 (December 2016) - Rosero, E.B.; Joshi, G.P.
Abstract : ( Acta Anaesthesiol Scand . 2016;60:810–820) Epidural analgesia (EA) is the gold standard for labor analgesia and provides effective pain relief after cesarean delivery. However, serious complications like spinal hematoma and abscess can occur. Currently, published data on the incidence of these complications are conflicting and involve variable methodology, sample size limitations, and exclusive patient populations. In order to address these issues, the authors of the present study used a large, administrative national database to describe the incidence of in-hospital spinal hematoma and epidural abscess associated with EA in obstetric and nonobstetric patients. They also investigated the factors associated with an increased likelihood of these complications.